Keanekaragaman Jenis Landak Laut Kelas Echinoidea di Pantai Kadahang Kabupaten Sumba Timur - Susani Rambu Anahau; Anita Tamu Ina (Bioscientist : Jurnal Ilmiah Biologi, 2023)
The purpose of this study was to determine the diversity of sea urchin species on the Kadahang Beach, East Sumba Regency. The sampling technique used is a purposive sampling and analyzed using a quantitative descriptive approach with the Shannon-Wiener diversity index formula. Sea urchin samples were calculated using the quadratic transect technique with a plot size of 1 x 1 meter placed perpendicular to the inside of 50 meters using a plot of 16 plots. The environmental factors measured were temperature, salinity, and acidity (pH). Measurements were carried out at two observation stations. The results showed that 8 species of sea urchin were divided into 4 orders, namely the orders Echinaceae, Diadematoida, Camarodonta, and Stomopnestes. The diversity index obtained is in the moderate category with a value of H` = 2.026.